A Multivariate State Estimation Technique and Multilayer Forward Neural Network Framework on Steam Turbine Valve Flow Curve Simulation. Issue 1 (June 2020) - Lu, Kuan; Wang, WenKuan; Meng, Xiangrong; Li, Jun; Pang, Xiangkun
Abstract: The Multivariate State Estimation Technique (MSET) is firstly implemented as the fault detection technique for monitoring parameters of the steam turbine valve. Second, healthy operation states are remained to form a preliminary dataset for the valve curve simulation. Then, the Forward neural network (FNN) based piecewise linear fitting method is used to simulate the steam turbine valve flow curve. With a MSET-FNN framework proposed, the simulation accuracy will be enhanced by removing the unhealthy operational states. In addition, the simulation process will gain a speed up with the utilization of GPU.